The Battlefield of Our Lives Tanztheater Wuppertal reviewed - Gilbert, Jenny (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Review of Tanztheater Wuppertal .
PALABRAS CLAVE: Tanztheater Wuppertal, Pina Bausch.
Keywords: Bausch, Pina -- 1940-2009; Tanztheater Wuppertal Pina Bausch